Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/2017ja024801
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Generation of Whistler Mode Chorus Emissions on the Temperature Anisotropy and Density of Energetic Electrons in the Earth's Inner Magnetosphere

Abstract: We carry out a series of self‐consistent electron hybrid code simulations for the dependence of chorus generation process on the temperature anisotropy and density of energetic electrons in the Earth's inner magnetosphere. We use the same magnetic field gradient in the simulation system and different temperature anisotropy AT for the initial distribution of energetic electrons at the magnetic equator. We conduct 6 sets of simulations for different AT from 4 to 9, changing the initial number density Nh of energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 45 publications
2
30
3
Order By: Relevance
“…The hot/source electron density nh affects Bop and amplitude growth rate. We set a proper ratio of hot electron density to cold electron density nhfalse/ne=0.005, which is a reasonable value based on observations and simulations (e.g., Juhász et al, ; Katoh et al, ; Kurita et al, ; Santolík et al, ). The parameters used for the wave generation are listed in Table .…”
Section: Simulation Methodsmentioning
confidence: 99%
“…The hot/source electron density nh affects Bop and amplitude growth rate. We set a proper ratio of hot electron density to cold electron density nhfalse/ne=0.005, which is a reasonable value based on observations and simulations (e.g., Juhász et al, ; Katoh et al, ; Kurita et al, ; Santolík et al, ). The parameters used for the wave generation are listed in Table .…”
Section: Simulation Methodsmentioning
confidence: 99%
“…Both of these currently limit the usability of these codes for studying radiation belts electron dynamics during long time periods (e.g., >2 days). Test‐particle codes are used to investigate the self‐consistent nonlinear mechanism of wave generation and growth in the radiation belts (e.g., Omura et al, 2009; Hikishima et al, ; Omura & Zhao, , ; Chen et al, ; Katoh et al, ; Omura et al, ). Nevertheless, wave particle interaction in this context is at the forefront of the field, with, for instance, Omura et al () using test particle simulation for studying energetic electrons acceleration in resonant interaction with a chorus wave packet.…”
Section: New Radiation Belt Modeling Capabilities and The Quantificatmentioning
confidence: 99%
“…Since the values of R 2 for T LA , T NLA , D F , and D NF are all above 70%, the confidence levels are all good in the performance of the RF method. Here we note that Katoh et al () simulated the chorus development in terms of the number density of energetic electrons normalized by a fixed number density of cold electrons. They found that the threshold amplitude is smaller when the number density of energetic electrons is larger.…”
Section: An Evaluation Of Importance In Feature Variables By Random Fmentioning
confidence: 99%